Knowledge attitude and practice towards COVID-19 booster dose among health care workers: a cross sectional study - V., Arathy; Patil, Shailaja S.; Pattankar, Tanuja P. (International Journal Of Community Medicine And Public Health, 2024)
Background: Amidst the emerging COVID-19 variants worldwide, India started the COVID precautionary or booster dose vaccination by early 2022. Protecting the healthcare force is crucial, as they are critical drivers in increasing vaccine uptake among the public. Objective was to assess COVID-19 Booster dose vaccine coverage among Health Care Workers (HCWs) and to know the reasons for vaccine booster dose hesitancy. Methods: A cross-sectional study was conducted among health care workers in Vijayapura city, during April-May 2022. The questionnaire in google form was shared to the target population, wherever necessary phone in interview was done. Data was tabulated in MS office Excel and analyzed using appropriate statistical tests. Results: Out of 275 participants from different levels of health care system, 50% were males, 75% in age group <40 years and 67% were from urban area. 37% of the participants took precautionary dose of vaccine against COVID-19. Among those who did not take a booster shot, 22.5% were hesitant to take the vaccine and the reasons were: “Lack of faith in vaccination”, “two doses are sufficient”, and “Fear of side effects”. Socio demographic factors such as age, gender and residence were found to be statistically significant with the COVID Booster vaccination status. Conclusions: Majority health workers are aware of booster dose vaccination, reasons for not taking booster dose were mainly lack of need and fear of side effects.